(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
Casson fluid flow with variable viscosity in porous media over a heated stretching sheet is investigated. The partial differential equations representing the flow motion are first transformed to ordinary differential equations by similarity transformation before being solved numerically by the finite-difference method. The effects of the viscosity variation parameter \((Ω)\), the permeability number \((κ)\), Prandtl number \((Pr)\), Biot number \((Bi)\) and non-Newtonian fluid parameter \((β)\) on the fluid flow and heat transfer, along with the temperature and velocity profiles, are presented graphically for some arbitrary values.